2012
DOI: 10.1063/1.4754011
|View full text |Cite
|
Sign up to set email alerts
|

Conduction mechanisms at low- and high-resistance states in aluminum/anodic aluminum oxide/aluminum thin film structure

Abstract: In this work, conduction mechanisms of Al/anodic Al oxide/ Al structure, which exhibits resistive switching behavior, have been investigated. The low-resistance state shows ohmic conduction with a metal-like behavior similar to that of pure aluminum. The situation can be explained by the existence of the metallic filament formed by the excess Al in the Al oxide. On the other hand, the high-resistance state (HRS) shows two distinct regimes: ohmic conduction at low fields with a semiconductor-like behavior; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…Zhu et al [36] observed that the anodic-AlOx device with homogenous Al electrode is fit to both P-F and Schottky emission expression. Since symmetrical check on I-V relation is not possible due to homogenous electrodes, Zhu et al resorted to compare the activation energies (Ea) extracted from the respective Arrhenius plots, but found that the extracted values are close (0.41-0.43 eV) and indecisive.…”
Section: Similar Asymmetrical Property Of I-v Relation Is Also Witnesmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhu et al [36] observed that the anodic-AlOx device with homogenous Al electrode is fit to both P-F and Schottky emission expression. Since symmetrical check on I-V relation is not possible due to homogenous electrodes, Zhu et al resorted to compare the activation energies (Ea) extracted from the respective Arrhenius plots, but found that the extracted values are close (0.41-0.43 eV) and indecisive.…”
Section: Similar Asymmetrical Property Of I-v Relation Is Also Witnesmentioning
confidence: 99%
“…Hence, the existence of Schottky emission can be ascertained by fitting to two functions, which are: (i) ln(J/T 2 ) ∝ 1/T under fixed electric field; and (ii) ln(J) ∝ E 1/2 under fixed temperature. There are numerous published resistive switching devices that suggested Schottky emission as the dominant conduction mechanism, such as [33][34][35][36][37][38][39][40][41][42], etc. The combination of electrodes and materials of these works is listed in Table 3.…”
Section: Schottky Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…5(a) shows double-logarithmic J-V plots at the positive voltage (that is, substrate injection) for Au/ZrO 2 /n-Si devices. The weak temperature dependence for J-V characteristics suggests that the space charge limited current (SCLC) can be considered as the main conduction mechanism [25]. Within the positive voltage region, the slope is very close to linear in the low voltage region, which corresponds to the Ohmic law region (J-V).…”
Section: Resultsmentioning
confidence: 98%
“…This indicates that current conduction represents Ohmic conduction with metal-like behavior due to phonon scattering of the electrons transportation in the filament. 15 The Ohmic conduction with metal-like behavior in untreated Zn:SiO x thin film can be explained by accumulation of excessive metal phase zinc, which may lead to the formation of metallic filament. Ohmic conduction is further testified by current fitting, which was shown as the bottom left inset of Fig.…”
mentioning
confidence: 99%